Answer:
A = 3
Step-by-step explanation:
Given
(5x² + 3x + 4) - (2x² + 5x - 1)
Remove the parenthesis from the first and distribute the second by - 1
= 5x² + 3x + 4 - 2x² - 5x + 1 ← collect like terms
= 3x² - 2x + 5
In the form Ax² + Bx + C
with A = 3
Answer:
Assuming this is the full problem.
3x^2-8x+4
Step-by-step explanation:
19.30 - ( p / 100 )*19.32 = 14.01 ;
19.30( 1 - p/100 ) = 14.01 ;
1 - p/100 = 14.01 / 19.30
1 - p / 100 = 0.72 ;
p/100 = 1 - 72 / 100 ;
p/100 = 28 / 100 ;
p = 28 ;
The percent discount is 28% ;